APAKAH ELEMEN CORPORATE GOVERNANCE DAPAT MENGURANGI FINANCIAL DISTRESS PADA PERUSAHAAN BERISIKO TINGGI? - Isnaini Nuzula Agustin; Andryanto (Jurnal Bisnis dan Akuntansi, 2023)
This study examine the role of Corporate governance (proxied by audit committee independence variables, institutional ownership, independent commissioners, board size) and enterprise risk management in predicting the emergence of corporate financial distress. The research design is quantitative. The research object or population studied is mining companies listed on the Indonesia Stock Exchange (IDX) during the period of 2016-2021. The method used for determining the research sample is purposive sampling, namely determining the sample from the existing population based on predetermined criteria obtaining research sample of 132 observations. All data sets are sourced from the Indonesia Stock Exchange website. This study is employing Panel Regression Analysis including descriptive statistics analysis, correlation, and hypothesis testing using the EViews 12 software. The result posits that institutional ownership has a significant positive effect on financial distress, while the independence of the audit committee, independent commissioners, board size, enterprise risk management do not have a significant impact on financial distress. Further, the control variable of this study, namely company size, has a significant negative effect on financial distress. This study is expected to have significant contribution to Mining enterprise’s stakeholder in examining prominent factors in predicting financial distress.